Jesuit promotion of social justice: Social justice action at Jesuit universities in Spain, as assessed by teaching and research staff - Vivanco, Borja (British journal of religious education, 2018)
A substantive and differentiating element of the Jesuits' university paradigm is the promotion of social justice. The results of a telephone poll conducted amongst professors and researchers convey the initiatives to further social justice that Jesuit universities in Spain have been carrying out primarily since the 1990s. Although still a limited presence, respondents largely favour continuing said initiatives.